Luigi Einaudi. Un economista e un liberale a Torino - Becchio, Giandomenica (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
Being the major figure within the school of economics, which has been developed in Torino between the end of XIX century and World War II, Luigi Einaudi was a master amongst intellectuals and economists in the history of Italian classical liberalism. The aim of this paper is to highlight the peculiar feature of his political liberalism, to be intended as the most important consequence of economic liberalism, as it has been emphasized by the well- known querelle Einaudi-Croce as well as by the influence Pareto and neoclassical economics had on him.